The role of strategic changes in the management of an enterprise in modern conditions - Shirinov, B. H. o.; Musayev, R. J. о.; Ширінов, Б. Х. o.; Мусаєв, Р. Д. о. (Харківський національний автомобільно-дорожній університет, 2025)
In the context of dynamic market environments and institutional transformation, enterprises are increasingly challenged to implement strategic changes that ensure sustainability and competitiveness. Organizational culture, innovation infrastructure, and adaptive management models represent critical dimensions of such transformation, yet their interdependence is often underestimated in traditional approaches. The purpose of this study is to systematize and adapt modern approaches to strategic change management, highlighting the integration of organizational, cultural, technological, and innovation-oriented factors. The results demonstrate that successful implementation of strategic change requires coordinated preparation of personnel, development of innovation systems, and the adoption of flexible management models. Employee readiness, supported through consistent training, staged adaptation, and clear communication of objectives, reduces resistance and fosters engagement. At the same time, innovation infrastructure and information technologies play a central role in supporting decision-making processes and enhancing the responsiveness of enterprises to market demands. Modern models such as forward-looking, network-based, agile, and customer-oriented organizations provide the structural and operational flexibility required to compete under conditions of uncertainty. The scientific contribution of the article lies in the integration of these dimensions into a comprehensive framework for guiding enterprises through complex transformations. Unlike traditional approaches that prioritize either structural or technological elements, the proposed framework demonstrates that sustainable competitiveness depends on balancing human, cultural, and technological resources. The practical significance of the study is expressed in the possibility of applying this framework as a diagnostic tool for assessing readiness for change and as a roadmap for enterprise-specific transformation strategies. The findings are particularly relevant for enterprises in transition economies, where limited resources and external shocks require adaptive, innovation-driven, and culturally sensitive approaches to strategic management.
Роль стратегічних змін у менеджменті підприємства в сучасних умовах
Keywords: strategic changes; organizational structure; planning; marketing; human resources; consumers; innovation; coordination; enterprise; management; стратегічні зміни; організаційна структура; планування; марке- тинг; людські ресурси; споживачі; інновації; координація; підприємство; менеджмент; 330.3: 658.012.2; 10.30977/ЕТК.2225-2304.2025.46.87